Autosomal Recessively Inherited Glucose Transporter-1 Deficiency Syndrome with Acanthocytosis: A Case Report - Wanigasinghe, Jithangi; Jayasundara, Kasun; Jasinghe, Eresha (Journal of Pediatric Neurology, 2023)
Glucose transporter-1 deficiency syndrome (GLUT-1DS) is a rare, autosomal dominantly inherited disorder due to a heterozygous mutation in the gene solute channel 2A1 (SLC2A1).This gene encodes the glucose transporter protein-1. Autosomal recessive inheritance is extremely rare. Similarly, only very few reports are found in the literature of hematological manifestations in this syndrome. We report an autosomal recessively inherited GLUT-1DS, due to a de novo mutation, with the classical infantile presentation associated with concomitant acanthocytosis. In this case report, the second child born to consanguineous parents with initial refractory neonatal seizures and subsequent poorly controlled epilepsy and developmental regression is discussed. The most notable investigation findings supportive of his underlying diagnosis were very low cerebrospinal fluid (CSF) glucose and CSF lactate levels. His CSF:plasma glucose ratio was 1:7.6. He was anemic with a hemoglobin of 8.8 g/dL with his blood film showing marked acanthocytosis. His elder brother who also had refractory epilepsy and developmental regression had similar hypoglycorrhachia, low CSF:plasma glucose ratio, and mild anemia with acanthocytosis, and he died before establishment of a diagnosis. Our patient was diagnosed to have a novel mutation SLC2A1 c.184A > G p.(Thr62Ala), for which both parents were heterozygous, confirming autosomal recessive inheritance. Commencement of a ketogenic diet resulted in improvement of his seizures and slow gain in development. It also resulted in gradual disappearance of acanthocytes from his peripheral blood. This case describes a rare case of classical GLUT-1DS, autosomal recessively inherited, due to a novel mutation. The acanthocytosis in his blood smear is another rare association minimally reported in GLUT-1DS. The cause of his abnormal red blood cell morphology is unclear. It is possibly related to cation leakage reported in some rare mutations of the SLC2A1 gene needs reference.
Keywords: classical; glucose transporter-1 deficiency syndrome; red cell morphology